Simulation of Interaction Processes of C20 Fullerene with Graphene - Ishmumin D. Yadgarov; Farid F. Umarov; Asroriddin S. Kosimov; Khayitmurod I. Jabborov; Shodibek Y. Aminov (East European Journal of Physics, 2023)
Graphene, a carbon sheet one atom thick, with carbon atoms arranged in a two-dimensional honeycomb configuration, has a number of intriguing properties. Fullerenes are a promising material for creating electro-active elements in solar cells and active layers in thin-film organic transistors. A computer model of the C20 fullerene molecule was constructed using the energy minimization method with the second-generation Brenner potential (REBO). A computer model of "infinite" defect-free graphene was built, designed to consider the process of adsorption of a C20 fullerene molecule on its surface. To study adsorption process computer models of fullerene and "infinite" graphene were approached to the required distance with a different set of geometric arrangement of fullerene with respect to the graphene surface. It has been established that the adsorption of fullerene C20 on the surface of graphene can be carried out in three different ways, differing in the number of interacting fullerene and graphene atoms. The binding energies and adsorption lengths for C20 fullerene molecules adsorbed on the graphene surface in different ways are calculated. The way of adsorption corresponding to the highest binding energy and the shortest adsorption length was revealed.